Immersive Virtual Reality Content Supporting a Wide and Free Viewpoint Made With a Single 360° Camera - Hyunmin Jung; Hyuk-Jae Lee; Chae Eun Rhee (IEEE Access, 2023)
Light field (LF)-based virtual reality (VR) systems have been proposed to tackle the problem of 360° panoramic image based VR not being able to support viewpoint movements. LF-based approaches still have shortcomings in that the user’s movement range is narrow and an extensive setup and high cost are required for data acquisition. This paper proposes lawn mowing pattern LF (LMP-LF) structure and presents a wide and free VR system utilizing an LMP-LF. The contributions of this paper are as follows. First, this paper proposes an LMP-LF in which several three-dimensional LFs (3DLFs) are arranged at uniform intervals. This simplifies the data acquisition process and widens the range of viewpoint movements. Second, this paper defines a light ray pair between two adjacent 3DLFs of the LMP-LF. The relationship between two light rays forming a light ray pair is expressed only with one-dimensional (1D) disparity, which greatly reduces the amount of disparity and the estimation complexity. Third, a real-time VR system using the LMP-LF is implemented and demonstrated. The proposed VR system achieves a high rendering speed of 125 frames-per-second (fps). In the prototype system, wide and free rendering performance was verified by building an LMP-LF for an automobile showroom at a size of 50m2.